Free Vibration and Buckling Analysis of Tapered Beam with Open Transverse Crack - Dr. Rambha Thakur, Firoj Ali (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
Tapering beams are used in diversities for their economic, aesthetic and other considerations in architecture, aeronautics, robotics and other innovative engineering applications. More recently they have been the subject of numerous studies. Present study deals with the vibration and buckling behavior of linearly tapered beams with single open transverse cracks. The variety of natural frequency and buckling load with distinctive parameters including relative crack depth, position of cracks and the slope of the beam are analyzed using finite element methods (FEM). A Matlab code is developed for the computation of natural frequencies and buckling loads of the cracked beam.